So, you want to be a writer? : how to write, get published, and maybe even make it big! - Hambleton, Vicki (Aladdin : Beyond Words, 2012)
"Join a select group of authors--from Stephen King to Cameron Crowe--all of whom published their first works before turning eighteen. So, You Want to Be a Writer? is the only hip how-to book that walks you through every step of the process, from generating ideas to marketing a book. You'll learn: how to battle the dreaded writer's block. - exercises to improve your storytelling skills. - how to find an agent and get published. - the ins and outs of publishing. - how to promote your unique work. - and more! With a complete glossary of terminology used by publishers and agents, a step-by-step guide to writing and finishing your book, exclusive insights from famous authors, and a complete list of magazines, websites, contests, and book publishers on the lookout for new writers, So, You Wanna Be a Writer? can be your first and last stop to success!"-- Provided by publisher.